Foreign Corrupt Practices Act : a practical resource for managers and executives - Murphy, Aaron G. (Wiley, 2011)
"This book is a practical business guide for managers and executives covering bribery and FCPA compliance issues that they need to understand to ensure they are not exposing their organization to charges. While it stands alone and is a great resource for those interested in understanding these issues for their own professional growth, it is also meant to be used as a training tool by organizations who wish to mitigate their risk to FCPA violations. The author plans to include a certification page that employees sign and return for inclusion in their personal files"--